Manufacturing Strategies for a Family of Integrated Photovoltaic-Fuel Cell Systems - Chukwuma Ogbonnaya; Grace Hegarty (Energies)
Integrated photovoltaic-fuel cell (IPVFC) systems have the potential to contribute to sustainable energy production for grid and off-grid applications. While there are studies focusing on fundamental science and designs for IPVFC systems, there are few studies that have focused on the manufacturability of IPVFC systems, which is certainly the pathway for the commercialisation of the systems. This study explores manufacturing strategies that can be considered for exploiting a family of eleven IPVFC systems. A survey and systems thinking approach were used to investigate the potential modularisation and supply chain management of the systems to achieve an optimal lean and agile manufacturing strategy. Results show that the Photovoltaic-Thermal-Separate Converter-Inverter-Battery System received 25% of the responses. The optimal manufacturing strategy depends on the overall business strategy of the firm. The 17% preference for System 1 was significant compared to four members of the family of IPVFC systems (Systems 2, 6, 8 and 9) that received only 2% of the responses, and there is a likelihood that the demand for System 1 will be among the top 42% of the total demand of all the systems. Overall, this study provides new insights into how the family of IPVFC systems can contribute to realising greater access to cleaner energy, by extension contributing to net-zero efforts using solar energy and solar hydrogen.